2013
DOI: 10.1093/scan/nst058
|View full text |Cite
|
Sign up to set email alerts
|

The association of interoceptive awareness and alexithymia with neurotransmitter concentrations in insula and anterior cingulate

Abstract: Alexithymia and increased interoceptive awareness have been associated with affective disorders as well as with altered insula and anterior cingulate cortex (ACC) function. Brain imaging studies have demonstrated an association between neurotransmitter function and affective disorders as well as personality traits. Here, we first examined the relationship between alexithymic facets as assessed with the Toronto Alexithymia Scale (TAS-20) and interoceptive awareness (assessed with the Body Perception Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 99 publications
10
87
3
4
Order By: Relevance
“…Similar to the accounts of reduced registration of emotional arousal, there appears to be a disconnect between general physiological/somatic activity and conscious awareness of sensation in individuals with high alexithymia (Grynberg and Pollatos 2015). This is reflected in findings of poorer bodyperception, such as reduced registration of the effects of chemical intake or poorer perception of own heart beat (Ernst et al 2014;Herbert et al 2011;Lyvers et al 2014). Furthermore, individuals with alexithymia experience less pleasure during relaxation and report more boredom, with suggestions they may find it difficult to engage with and derive pleasure from the stimulation in their environment (Eastwood et al 2007;Eastwood et al 2012;Friedlander et al 1997).…”
Section: The Association Between Alexithymia and Sensory Sensitivitiesmentioning
confidence: 68%
See 1 more Smart Citation
“…Similar to the accounts of reduced registration of emotional arousal, there appears to be a disconnect between general physiological/somatic activity and conscious awareness of sensation in individuals with high alexithymia (Grynberg and Pollatos 2015). This is reflected in findings of poorer bodyperception, such as reduced registration of the effects of chemical intake or poorer perception of own heart beat (Ernst et al 2014;Herbert et al 2011;Lyvers et al 2014). Furthermore, individuals with alexithymia experience less pleasure during relaxation and report more boredom, with suggestions they may find it difficult to engage with and derive pleasure from the stimulation in their environment (Eastwood et al 2007;Eastwood et al 2012;Friedlander et al 1997).…”
Section: The Association Between Alexithymia and Sensory Sensitivitiesmentioning
confidence: 68%
“…On the one hand, individuals with elevated alexithymia can exhibit hypersensitivity to sensory input, such as lower tolerance of pain and heat, and over responsiveness to visceral stimulation (Kano et al 2007;Katz et al 2009;Nyklicek and Vingerhoets 2000). On the other hand, they also show reduced awareness and registration of internal bodily signals (Ernst et al 2014). …”
Section: Alexithymia and Sensory Processing Atypicalitiesmentioning
confidence: 99%
“…However, we have recently shown that when OXT suppresses amygdala responses, other brain regions including the insula may become more influential in biasing cognitive and emotional processing towards increased preparedness for self‐defense [Striepens et al, ]. The insula is also important for self‐processing and interoceptive awareness [Ernst et al, ; Lamm and Singer, ] and so OXT may potentially be producing a heightened sense of self which can in turn lead to increased perspective‐taking and empathic concern. Other regions implicated in self‐processing include a number of cortical midline regions which form part of the default‐mode network (DMN), most notably the medial prefrontal cortex, cingulate cortex, and precuneus [Qin and Northoff, ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found moderately negative associations between alexithymia and body awareness (21)(22)(23), suggesting that a lack of ability to identify and verbalize emotions may be related to a lack of awareness of physical sensations.…”
mentioning
confidence: 97%